CHARACTERISTICS OF OPHIOLITE-RELATED METAMORPHIC ROCKS IN THE BEYSEHIR OPHIOLITIC MÉLANGE (CENTRAL TAURIDES, TURKEY), DEDUCED FROM WHOLE ROCK AND MINERAL CHEMISTRY - Çelik O.F.; Delaloye M.F. (My University, 2006)
Small outcrops of the metamorphic rocks of the Beysehir ophiolite appear to the west of Gencek and to the south of Durak (South of Beysehir Lake) in the Central Tauride Belt in Turkey. Amphibolitic rocks in the ophiolitic mélange have an igneous origin. Protoliths of these rocks were probably alkali basalts, gabbros or some ultramafic cumulates, such as pyroxenite. The amphibolites of the Beysehir Ophiolite can be divided into four groups: (1) amphibole+garnet+plagioclase±epidote (as secondary minerals)±opaque such as ilmenite±accessory minerals such as sphene and apatite; (2) amphibole+pyroxene+plagioclase±epidote±accessory minerals such as sphene, apatite±chlorite, calcite (as secondary mineral); (3) amphibole±plagioclase±opaque±accessory minerals; (4) amphibole+plagioclase±epidote±biotite and muscovite±opaque±accessory minerals. These metamorphic rocks show mainly granoblastic, grano-nematoblastic, porphyroblastic and/or poikiloblastic textures. All amphiboles in the amphibolites are calcic and cluster in the range from magnesio-hastingsite, pargasite to actinolite. Amphibole compositions are characterized by SiO2=(38.02-54.3%), Al2O3=(1.5-12.8), FeO=(10.03-14.67%), K2O=(0.2-1.8%), MgO=(5.5-15.7), Mg*=(0.3-0.8). The amphibolites show an alkaline to subalkaline character. However, the primitive mantle normalized incompatible trace element diagram shows close similarity with the typical ocean island basalt (OIB) pattern. The Rock/Chondrite normalized REE diagram of the amphibolites also confirms their OIB signature. Tectonomagmatic discrimination diagrams based on the immobile trace elements suggest a mostly within-plate alkali basalt (WPB) environment. Beysehir ophiolitic mélange contains amphibolites from ophiolite-related metamorphic rocks, but the matrix of the Beysehir ophiolitic mélange is not metamorphosed. Blocks of metamorphic rocks and the ophiolitic rocks may have been incorporated into the ophiolitic mélange in an oceanic environment during the Late Cretaceous by tectonic forces. © 2005 Elsevier Ltd. All rights reserved.
Keywords: AMPHIBOLITE; GEOCHEMISTRY; HYDROTHERMAL ALTERATION; MINERALOGY AND PETROGRAPHY; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая